Abortion and conscientious objection: Doogan – A missed opportunity for an instructive rights-based analysis. (September 2016) - Harmon, Shawn H.E.
Abortion is considered by some to be a morally questionable intervention, one which entitles the healthcarer to exercise conscientious objection (CO) so as to opt out of acting. The healthcarer's right to do so was recently considered by the UK Supreme Court (UKSC) in Greater Glasgow Health Board v. Doogan and Wood, a case which set some boundaries on CO but which failed to engage holistically with the foundation of CO and its position relative to the competing right to adequate healthcare, a failure which must be seen as a lost opportunity given the manifold threats to timely access to abortion. This article fills the lacunae. After noting the weaknesses in the Doogan judgement, it justifies the adoption of a more robust approach by the UKSC, and then analyses the moral and rights foundations of abortion and CO, noticing as it does the growing practical problem that is the expansion and misuse of CO in women's health (i.e. its deployment as a barrier to women seeking lawful abortion services). It concludes that courts everywhere, but particularly in jurisdictions that are widely persuasive, such as the United Kingdom, when faced with the opportunity to pronounce on the right to abortion and the operation of CO, should take full advantage, and in doing so, should adopt a critical and restrictive approach to its availability in the healthcare context.